Effect of recycled aggregate concrete with glass fiber on concrete properties - Ahmed Al-Hamed, Ahmed Hasan (2019)
Waste materials have becoming an issue worldwide nowadays. From construction to transportation, all these wastes contribute to serious environmental problem. Therefore, an urgent need of an alternative in reducing the waste is highly recommended. In this study, recycle aggregate concrete (RAC) obtained from crushed concrete and glass fiber are used in the concrete mix. Furthermore, concrete made from glass fiber and recycled coarse aggregate as partial replacement of coarse aggregate is studied for workability, compressive and flexural strengths. In this study, recycled coarse aggregate used as partial replacement of coarse aggregate by percentage replacement 20% with natural aggregate. Glass fiber was used to replaced 1 % and 2 % of the total weight of cement. This study concentrated on the workability, compressive strength and flexural strength of the RAC with different percentage of glass fiber. One test was conducted for workability of fresh RAC namely slump test. Meanwhile, cubes were subjected to compressive strength test and beams were subjected to flexural strength test. All the specimens were cured in water for 7and 28 days. The results indicated that the fresh RAC exhibit a significant decrease in workability with increasing percentage of glass fiber. However, the strength of the recycle aggregate concrete is increasing with increased percentage of glass fiber. This is due to the physical properties of the RAC and glass fiber. In general, the results suggested that the glass fiber used to replace the cement should be more than 2 % in order to achieve higher strength.